Bismuth-modified and the native tricresyl phosphate-based carbon paste electrode for the determination of two different pesticides - Đorđević, Jelena; Rodić, Marko; Ashrafi, Amir; Papp, Zsigmond; Guzsvány, Valéria; Trtić-Petrović, Tatjana; Švancara, Ivan; Vytřas, Karel (Univerzita Pardubice, 2012)
In this article, the voltammetric responses of the bismuth powder bulk-modified tricresyl phosphate-based carbon paste electrode (Bi5%-C/TCP, where 5% is the content of pulverized metal), surface-modified, bismuth film-plated BiF-C/TCP), and the unmodified carbon paste electrode of the C/TCP type were studied and subsequently optimized for the cathodic determination of Imidacloprid (IMI), an insecticide reducible in a fairly negative potential range. The individual comparisons have shown that the determination of IMI is more efficient with the Bi5%-C/TCP or Bi20%-C/TCP, respectively, by the direct cathodic differential pulse voltammetry (DPV). Concerning the determination of Carbendazim (CBZ), a fungicide oxidizable at the positive potentials, the unmodified C/TCP was applied to the determination in the differential pulse anodic stripping voltammetric mode. The respective LODs were at the low μg mL-1 level for IMI or even down to the ng mL-1 for a more sensitive determination of CBZ.
Keywords: tricresyl phosphate-based carbon paste; two bismuth-modified variants; unmodifed form; voltammetric determination; imidacloprid (IMI); carbendazim (CBZ)